Old-age security in Bhutan: From lump-sum payments towards a pension scheme - Winfried Schmähl (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2002)
At present, Bhutan's old-age security still is mostly based on an extended family network. Formal old-age provision mainly is for civil servants, providing, however, only lump-sum payments. This paper analyses the present conditions and obvious deficits of the existing arrangements and outlines possibilities for introducing a pension scheme which provides regular (monetary) income in old age. Income in old age could be increased and costs could be reduced by transforming the existing Provident Fund totally or partially into a pension scheme. This can be combined with pay-as-you-go and funded elements.
Keywords: 300